1986
DOI: 10.1159/000118668
|View full text |Cite
|
Sign up to set email alerts
|

Brain Stem Auditory Nuclei and Their Connections in a Carnivorous Marsupial, the Northern Native Cat <i>(Dasyurus hallucatus)</i>

Abstract: The cytoarchitecture and connections of the brain stem auditory nuclei in the marsupial native cat (Dasyurus hallucatus) were studied using Nissl material in conjunction with the retrograde transport of horseradish peroxidase injected into the inferior colliculus. Some features different from those of Eutheria include the disposition of the cochlear nuclear complex medial to the restiform body, a lack of large spherical cells in the anteroventral cochlear nucleus, a small medial superior olive, and a large sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 15 publications
6
15
0
Order By: Relevance
“…The inter- nal organization of this rather sparsely populated complex is similar to that described for opossums [7] and marsupial native cats [4]. A medial superior oliva ry nucleus contains bipolar cells arranged in a trun cated column that gradually spreads ventrally into the ventral nucleus of the trapezoid body (VTB; fig.…”
Section: Anatomy Of the External Ear Canalsupporting
confidence: 60%
See 1 more Smart Citation
“…The inter- nal organization of this rather sparsely populated complex is similar to that described for opossums [7] and marsupial native cats [4]. A medial superior oliva ry nucleus contains bipolar cells arranged in a trun cated column that gradually spreads ventrally into the ventral nucleus of the trapezoid body (VTB; fig.…”
Section: Anatomy Of the External Ear Canalsupporting
confidence: 60%
“…In other marsupials examined [4][5][6][7] the dorsal cochlear nucleus forms a bulge, ventral to the fourth ventricle and medial to the inferior cerebellar peduncle, and has a characteristic layered structure. The most superficial (molecular) layer is sparsely populated with small cells, the py ramidal cell layer consists of a regular row of large cells with accompanying granule cells, and the deep (polymorphic) layer contains a variety of neuronal types including the largest cells in the dorsal cochlear nucleus.…”
Section: Anatomy Of the External Ear Canalmentioning
confidence: 99%
“…The projection from the MSO to the IC is largely or entirely ipsilateral in many mammals, including cat, rat, gerbil, bat and ferret (Adams, 1979;Coleman and Clerici, 1987;Glendenning and Masterton, 1983;Moore, 1988;Nordeen et al, 1983;Okoyama et al, 1995b;Zook and Casseday, 1982). On the other hand, in some primitive species such as the mole (Mogera), opossum (Didelphis) and northern native cat (Dasyurus), the MSO has been shown to project bilaterally to the IC (Aitkin et al, 1986;Kudo et al, 1990a;Kudo et al, 1990b;Kudo et al, 1988;Willard and Martin, 1983;Willard and Martin, 1984). Double-labeling studies in the mole (Kudo et al, 1990a) and opossum (Willard and Martin, 1984) have demonstrated that many MSO neurons are double-labeled with different tracers injected separately into left and right IC, indicating that these double-labeled neurons project bilaterally via axon collaterals.…”
Section: Methodsmentioning
confidence: 99%
“…In the three experiments on the inferior collicu lus, a small hole was drilled through the occipital bone and the dura mater was removed to reveal the colliculi, which are not covered by cortical or cere bellar tissue in this species -see figure 1 in Aitkin et al [2]. Microelectrode penetrations were made ap proximately dorsoventrally through the inferior col liculus.…”
Section: Methodsmentioning
confidence: 99%
“…Very little is known of the functional organization of the auditory system in marsupials, although there are detailed de scriptions of lower auditory connections in three marsupial species [2,4,19] and a description of thalamocortical auditory projections in one of these, the brush tailed possum [3]. Some information about tonotopic organization is available for the inferior colliculus [1] and auditory cortex [8] of brush-tailed possums.…”
Section: Introductionmentioning
confidence: 99%